Masked hypoglycemia in pregnancy: 妊娠期隐性低血糖. (14th November 2016) - Naik, Dukhabandhu; Hesarghatta Shyamasunder, Asha; Doddabelavangala Mruthyunjaya, Mahesh; Gupta Patil, Rita; Paul, Thomas Vizhalil; Christina, Flory; Inbakumari, Mercy; Jose, Ruby; Lionel, Jessie; Regi, Annie; Jeyaseelan, P. Visalakshi; Thomas, Nihal
Abstract: Background: Hypoglycemia is a major hindrance for optimal glycemic control in women with gestational diabetes mellitus (GDM) on insulin. In the present study, masked hypoglycemia (glucose <2.77mmol/L for ≥30 min) was estimated in pregnant women using a continuous glucose monitoring (CGM) system. Methods: Twenty pregnant women with GDM on insulin (cases) and 10 age‐matched euglycemic pregnant women (controls) between 24 and 36 weeks gestation were recruited. Both groups performed self‐monitoring of blood glucose (SMBG) and underwent CGM for 72 h to assess masked hypoglycemia. Masked hypoglycemic episodes were further stratified into two groups based on interstitial glucose (2.28–2.77 and ≤2.22 mmol/L). Results: Masked hypoglycemia was recorded in 35% (7/20) of cases and 40% (4/10) of controls using CGM, with an average of 1.28 and 1.25 episodes per subject, respectively. Time spent at glucose levels between 2.28 and 2.77 mmol/L did not differ between the two groups (mean 114 vs 90 min; P = 0.617), but cases spent a longer time with glucose ≤2.2 mmol/L. Babies born to women with GDM were significantly lighter than those born to controls (2860 vs 3290 g; P = 0.012). There was no significant difference in birth weight within the groups among babies born to women with or without hypoglycemia. Conclusion: Euglycemic pregnant women and those with GDM on insulin had masked hypoglycemia. Masked hypoglycemia was not associated with adverse maternal or fetal outcomes. Therefore, low glucose levels in the hypoglycemic range may represent a physiologic adaptation in pregnancy. This response is exaggerated in women with GDM on insulin. Abstract : Continuous glucose monitoring profiles in women with gestational diabetes mellitus on insulin (a) with or (b) without masked hypoglycemia. Graphs show glucose profiles in individual women over 72 h. (a) In women with GDM and masked hypoglycemia, the episodes of masked hypoglycemic occurred mostly during the night (2300–0600 h), corresponding to values numbered 124–230, 432–518, and 720–820 (on the first, second and third nights, respectively). (b) In women with GDM but no masked hypoglycemia, there was a trend towards lower glucose values at night (2300–0600 h), corresponding to values numbered 124–230, 432–518, and 720–820, but these values were above 2.77 mmol/L (50 mg/dL). Highlights Glucose dynamics in pregnancy are altered, with a trend towards lower fasting levels in the hypoglycemic range. Euglycemic pregnant women, as well as those with gestational diabetes mellitus on insulin, experienced masked hypoglycemia, which may be a physiologic adaptation in pregnancy. Hypoglycemic episodes did not adversely affect maternal or fetal outcomes. Continuous glucose monitoring uncovered masked hypoglycemia in pregnancy. This was not associated with adverse maternal or fetal outcomes, indicating that low glucose may be a physiologic adaptation.